Reciprocal mutations of lung-tropic AAV capsids lead to improved transduction properties - Cooney, Ashley L.; Brommel, Christian M.; Traore, Soumba; Newby, Gregory A.; Liu, David R.; McCray, Paul B.; Sinn, Patrick L. (Frontiers in Genome Editing, 2023)
Considerable effort has been devoted to developing adeno-associated virus (AAV)-based vectors for cystic fibrosis (CF) gene therapy. As a result of directed evolution and capsid shuffling technology, AAV capsids are available with widespread tropism for airway epithelial cells. For example, AAV2.5T and AAV6.2 are two evolved capsids with improved airway epithelial cell transduction properties over their parental serotypes. However, little effort has been devoted to identifying their specific cellular tropism. Restoring CFTR expression in surface columnar epithelial cells is necessary for correction of the CF airway phenotype. Basal cells are a progenitor population of the conducting airways responsible for replenishing surface epithelial cells (including secretory cells and ionocytes), making correction of this cell population vital for a long-lived gene therapy strategy. Here, we investigate the tropism of AAV capsids for three cell types in primary cultures of well-differentiated human airway epithelial cells as well as primary human airway basal cells. We observed that AAV2.5T transduced surface epithelial cells better than AAV6.2, while AAV6.2 transduced airway basal cells better than AAV2.5T. We also investigated a recently developed capsid AAV6.2FF which has two surface tyrosines converted to phenylalanines. Next, we incorporated reciprocal mutations to create AAV capsids with further improved surface and basal cell transduction characteristics. Lastly, we successfully employed a split intein approach using AAV to deliver an adenine base editor (ABE) to repair the R553X CFTR mutation. Our results suggest that rational incorporation of AAV capsid This is a provisional file, not the final typeset article mutations improves AAV transduction of airway surface and progenitor cells and may ultimately lead to improved pulmonary function of people with CF.